2016
DOI: 10.7717/peerj.2402
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary patterns of range size, abundance and species richness in Amazonian angiosperm trees

Abstract: Amazonian tree species vary enormously in their total abundance and range size, while Amazonian tree genera vary greatly in species richness. The drivers of this variation are not well understood. Here, we construct a phylogenetic hypothesis that represents half of Amazonian tree genera in order to contribute to explaining the variation. We find several clear, broad-scale patterns. Firstly, there is significant phylogenetic signal for all three characteristics; closely related genera tend to have similar numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 28 publications
6
51
0
1
Order By: Relevance
“…In previous studies, some traits showed low but significant PS [6,7,13], while others have even found that traits are randomly dispersed over the phylogeny [10,11]. However, although K -values are standardized to allow comparison between traits and phylogenetic trees [1,4], direct comparisons of PS are affected by differences in the spatial and taxonomic scale of the studies, the number of lineages and the use of different kinds of phylogenies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, some traits showed low but significant PS [6,7,13], while others have even found that traits are randomly dispersed over the phylogeny [10,11]. However, although K -values are standardized to allow comparison between traits and phylogenetic trees [1,4], direct comparisons of PS are affected by differences in the spatial and taxonomic scale of the studies, the number of lineages and the use of different kinds of phylogenies.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we use a large dataset of several hundred permanent forest plots that occur across a wide range of the environmental conditions from all nine Amazonian countries [26], to quantify key demographic traits of more than 300 lineages of tropical trees and explore the PS of these traits using recently published molecular genus- [13] and species-level phylogenies ([27], KG Dexter & RT Pennington 2013, unpublished data). By exploring how traits are correlated and the strength of PS, our goal is to address the fundamental question of whether repeated convergent and divergent evolution of life-history strategies has erased PS for life-history-related traits in tropical trees, or whether phylogenetic information can be used to understand ecosystem function in the world's most diverse and ecologically important forest.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, previously published lists of Amazon tree flora contain major errors (14,17,18), yet have been used in largescale analyses to infer patterns and processes of historical community assembly (e.g., ref. 18).…”
Section: Significancementioning
confidence: 99%
“…As discussed above, previously published lists of Amazon tree flora contain major errors (14,17,18), yet have been used in largescale analyses to infer patterns and processes of historical community assembly (e.g., ref. 18). It is difficult to draw conclusions regarding the ecological and evolutionary processes that have led to the assembly and maintenance of the Amazon tree flora based on a list of 631 genera, which includes 140 (22%) that do not occur in the Amazon or are not trees and omits 332 tree genera known to occur in the Amazon.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation